2021
DOI: 10.3390/plants10040694
|View full text |Cite
|
Sign up to set email alerts
|

An F2 Barley Population as a Tool for Teaching Mendelian Genetics

Abstract: In the context of a general genetics course, mathematical descriptions of Mendelian inheritance and population genetics are sometimes discouraging and students often have serious misconceptions. Innovative strategies in expositive classes can clearly encourage student’s motivation and participation, but laboratories and practical classes are generally the students’ favourite academic activities. The design of lab practices focused on learning abstract concepts such as genetic interaction, genetic linkage, gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 21 publications
3
2
0
Order By: Relevance
“…These results are roughly consistent with other surveys regarding Genetics teaching and learning, as the one reported by Giménez et al (2021) for a practical approach to strengthen the learning of Mendelian genetics using an ad hoc obtained population of barley. Nevertheless, the students in the present survey were more favorable to the advantages of practical approaches than those form Giménez et al (2021). Students in advanced courses, who often combine their studies with paid jobs, tend to show a more proactive attitude, with a better use of the time dedicated to study (Cao, 2012;Yun et al, 2020).…”
Section: Combined Use Of Simhyb 2 Genalex and Structure In Academic C...supporting
confidence: 92%
See 3 more Smart Citations
“…These results are roughly consistent with other surveys regarding Genetics teaching and learning, as the one reported by Giménez et al (2021) for a practical approach to strengthen the learning of Mendelian genetics using an ad hoc obtained population of barley. Nevertheless, the students in the present survey were more favorable to the advantages of practical approaches than those form Giménez et al (2021). Students in advanced courses, who often combine their studies with paid jobs, tend to show a more proactive attitude, with a better use of the time dedicated to study (Cao, 2012;Yun et al, 2020).…”
Section: Combined Use Of Simhyb 2 Genalex and Structure In Academic C...supporting
confidence: 92%
“…These results are roughly consistent with other surveys regarding Genetics teaching and learning, as the one reported by Giménez et al (2021) for a practical approach to strengthen the learning of Mendelian genetics using an ad hoc obtained population of barley. Nevertheless, the students in the present survey were more favorable to the advantages of practical approaches than those form Giménez et al (2021). Maybe a more mature attitude can account for this feature: Giménez et al reported a survey among second course, undergraduate students, 19-20 years old, while the students in the present work were in the second course of a master's degree, at least 24-25 years old.…”
Section: Combined Use Of Simhyb 2 Genalex and Structure In Academic C...supporting
confidence: 92%
See 2 more Smart Citations
“…Therefore, it is important to know how yield-related traits are inherited. Moreover, traits, including stably integrated transgenes and edited genes, are inherited according to Mendelian rules [27][28][29][30]. An exception to Mendel's principles that encompass both groups of genes is epigenetic inheritance [31] or the polygenic nature of genomic architecture for the linked traits, which can be regulated by transcription factors [32][33][34] or other gene regulatory networks [35].…”
Section: Introductionmentioning
confidence: 99%